Core Kubernetes. - Love, Christopher; Vyas, Jay (Manning Publications, 2022)
In Video Editions the narrator reads the book while the content, figures, code listings, diagrams, and text appear on the screen. Like an audiobook that you can also watch as a video. Take a deep dive into Kubernetes inner components and discover what really powers a Kubernetes cluster. This in-depth guide shines a light on Kubernetes' murky internals, to help you better plan cloud native architectures and ensure the reliability of your systems. In Core Kubernetes you will learn about: Kubernetes base components Kubernetes networking Storage and the Container Storage Interface External load balancing and ingress Kubernetes security Different ways of creating a Kubernetes cluster Configuring Kubernetes to use a GPU To build and operate reliable Kubernetes-based systems, you need to understand what's going on below the surface. Core Kubernetes is an in-depth guide to Kubernetes' internal workings written by Kubernetes contributors Chris Love and Jay Vyas. It's packed with experience-driven insights and advanced techniques you won't find anywhere else. You'll understand the unique security concerns of container-based applications, minimize costly unused capacity, and get pro tips for maximizing performance. Diagrams, labs, and hands-on examples ensure that the complex ideas are easy to understand and practical to apply. About the Technology Real-world Kubernetes deployments are messy. Even small configuration errors or design problems can bring your system to its knees. In the real world, it pays to know how each component works so you can quickly troubleshoot, reset, and get on to the next challenge. This one-of-a-kind book includes the details, hard-won advice, and pro tips to keep your Kubernetes apps up and running. About the Book This book is a tour of Kubernetes under the hood, from managing iptables to setting up dynamically scaled clusters that respond to changes in load. Every page will give you new insights on setting up and managing Kubernetes and dealing with inevitable curveballs. Core Kubernetes is a comprehensive reference guide to maintaining Kubernetes deployments in production. What's Inside Kubernetes base components Storage and the Container Storage Interface Kubernetes security Different ways of creating a Kubernetes cluster Details about the control plane, networking, and other core components About the Reader For intermediate Kubernetes developers and administrators. About the Authors Jay Vyas and Chris Love are seasoned Kubernetes developers. Quotes To understand the core details of Kubernetes, this is a must-read. - Ubaldo Pescatore, PagoPA A thorough overview of the important parts of Kubernetes. Clear language, plenty of detailed examples, and easy-to-understand diagrams. - Rob Ruetsch, adesso SE A detailed step-by-step guide that had me up and running in no time. Highly recommended! - Al Krinker, USPTO A perfect travel guide for the Kubernetes journey. - Gandhi Rajan, Software Dell Technologies.